Emergency department use by patients who received chimeric antigen receptor T cell infusion therapy - Lipe, Demis N.; Qdaisat, Aiham; Chaftari, Patrick; Wattana, Monica K.; Krishnamani, Pavitra P.; Reyes-Gibby, Cielito; Yeung, Sai-Ching J. (Frontiers in Oncology, 2023)
Background: Chimeric antigen receptor T cell infusion (CAR T) therapy has revolutionized the treatment of hematologic malignancies, but treatment-related toxicities are of concern. Understanding the timing and reasons for which patients present to the emergency department (ED) after CAR T therapy can assist with the early recognition and management of toxicities. Methods: A retrospective observational cohort study was conducted for patients who had undergone CAR T therapy in the past 6 months and visited the ED of The University of Texas MD Anderson Cancer Center between 04/01/2018 and 08/01/2022. The timing of presentation after CAR T product infusion, patient characteristics, and outcomes of the ED visit were examined. Survival analyses were conducted using Cox proportional hazards regression and Kaplan-Meier estimates. Results: During the period studied, there were 276 ED visits by 168 unique patients. Most patients had diffuse large B-cell lymphoma (103/168; 61.3%), multiple myeloma (21/168; 12.5%), or mantle cell lymphoma (16/168; 9.5%). Almost all 276 visits required urgent (60.5%) or emergent (37.7%) care, and 73.5% of visits led to admission to the hospital or observation unit. Fever was the most frequent presenting complaint, reported in 19.6% of the visits. The 30-day and 90-day mortality rates after the index ED visits were 17.0% and 32.2%, respectively. Patients who had their first ED visit >14 days after CAR T product infusion had significantly worse overall survival (multivariable hazard ratio 3.27; 95% confidence interval 1.29–8.27; P=0.012) than patients who first visited the ED within 14 days of CAR Tproduct infusion. Conclusion: Cancer patients who receive CAR T therapy commonly visit the ED, and most are admitted and/or require urgent or emergent care. During early ED visits patients mainly present with constitutional symptoms such as fever and fatigue, and these early visits are associated with better overall survival.